Quality analysis of translation of the first chapter of Vladimir Nabokov’s Lolita - Irene Nany K. (Jurnal Linguistik Terapan, 2013)
This article presents a result of translation quality analysis on the translation of Chapter One of Vladimir Nabokov’s “Lolita”. The result of the analysis shows that the translated text of Lolita, especially the first chapter, from English into Bahasa Indonesia by Anton Kurnia, still has some failures in delivering the message from its SL text (English). In one hand, the translator tries to maintain the delicacy of the wordplay used by the author, Vladimir Nabokov. On the other hand, the translator ignores the prominent function of the translation, which is to deliver the full message and to do so in such natural ways in the context of TL readers.